2015
DOI: 10.1002/jcb.25228
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PRIP (Phospholipase C‐Related But Catalytically Inactive Protein) in BMP‐Induced Smad Signaling in Osteoblast Differentiation

Abstract: Phospholipase C-related but catalytically inactive protein (PRIP) was first isolated as an inositol 1,4,5-trisphosphate binding protein. We generated PRIP gene-deficient mice which exhibited the increased bone mineral density and trabecular bone volume, indicating that PRIP is implicated in the regulation of bone properties. In this study, we investigated the possible mechanisms by which PRIP plays a role in bone morphogenetic protein (BMP) signaling, by analyzing the culture of primary cells isolated from cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…Contrary to our expectation, we found increased bone mineral density and trabecular bone volume in these mice, indicating that PRIP deficiency triggers bone mass increase as a result of increased bone formation and/or decreased bone resorption, independent of the reproductive hormone imbalance (26). We further determined that PRIP deficiency stimulates bone morphogenetic protein signaling, resulting in increased bone mass (27,28). However, the role of PRIP in osteoclastogenesis is not yet fully clarified.…”
contrasting
confidence: 89%
“…Contrary to our expectation, we found increased bone mineral density and trabecular bone volume in these mice, indicating that PRIP deficiency triggers bone mass increase as a result of increased bone formation and/or decreased bone resorption, independent of the reproductive hormone imbalance (26). We further determined that PRIP deficiency stimulates bone morphogenetic protein signaling, resulting in increased bone mass (27,28). However, the role of PRIP in osteoclastogenesis is not yet fully clarified.…”
contrasting
confidence: 89%
“…Culture medium was changed every 3 days. Primary osteoblasts isolated from the calvaria of newborn mice [37] were grown under 5% CO 2 in α-Minimum Essential medium containing 20% fetal bovine serum, 100 U/mL penicillin G, and 0.1 μg/mL streptomycin.…”
Section: Cell Culture and Osteoblast Differentiationmentioning
confidence: 99%
“…In 2015, Japanese researchers 17 demonstrated that PRIP was implicated in BMP‐induced osteoblast differentiation through negative regulation of Smad phosphorylation, which resulted from methylation of inhibitory Smad6. In 2017, these researchers demonstrated that PRIP deficiency impaired osteoclast differentiation, particularly at the early stages, and that PRIP stimulated osteoclast differentiation though calcium‐calcineurin‐NFATc1 signalling via regulation of intracellular Ca2+ in PRIP‐KO osteoclasts 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence is provided by osteoclast differentiation stimulated through calcium-calcineurin-NFATc1 signalling by regulating intracellular Ca 2+ in PRIP-KO osteoclasts. [15][16][17] Based on recent advances in elucidating the pathogenic mechanisms of GIONFH, we investigated the effects of biomechanical forces, bone metabolism and non-coding RNA in glucocorticoidinduced osteonecrosis of the femoral head. In this study, we observed the microstructure of femoral head in a rat model of GIONFH, before and after exercise on a treadmill or the tail suspension test that results in skeletal unloading.…”
Section: Patients With Gionfh In Arco (Association Researchmentioning
confidence: 99%
See 1 more Smart Citation